Ideal cardiovascular health and mortality: pooled results of three prospective cohorts in Chinese adults - Zhang, Y; Yu, C; Chen, S; Tu, Z; Zheng, M; Lv, J; Wang, G; Liu, Y; Yu, J; Guo, Y; Yang, L; Chen, Y; et al. (Wolters Kluwer, 2023)
Background: Evidence on the relations of the American Heart Association's ideal cardiovascular health (ICH) with mortality in Asians is sparse, and the interaction between behavioral and medical metrics remained unclear. We aimed to fill the gaps.